A highly malignant case of neuroblastoma with substantial increase of single-nucleotide variants and normal mismatch repair system: A case report - Yuan, Lin-Qing (Medicine (Baltimore), 2017)
RATIONALE: Neuroblastoma is a common abdominal malignancy in children. The chemoresistant and relapsed cases have poor prognosis. The genetic background and the mechanism of resistance remain unelucidated. Next-generation sequence (NGS) is becoming a popular tool to unravel the genetic background and to guide precision medicine in oncology studies as well as in clinical practice. PATIENT CONCERNS: Here we report a neuroblastoma case of a boy aged 2 years and 8 months when first diagnosed, with multiple metastatic sites found in both lungs. The metastatic tumors were resistant to chemotherapy and the patient suffered from severe bone marrow suppression. NGS of the whole exon revealed somatic mutations including 9666 single-nucleotide variants (SNVs) from 5148 genes, 55 copy number variations (CNVs), and 140 insertion–deletion variations. The high frequency of SNVs makes it distinguished case. However, no mutation of key tumor driver genes with functional significance was identified. No abnormality was found in nucleic acid synthesis enzymes. No amplification of c-Myc and n-Myc was found by fluorescence in situ hybridization (FISH). Both NGS and immunohistochemistry (IHC) analysis indicated that DNA mismatch repair (MMR) system was intact. INTERVENTIONS: After initial diagnosis, the patient received combinational chemotherapy, which includes vindesine, an analogue of adriamycin suggested by NGS data, for 4 months. Radical section of the tumor together with the left kidney and the left adrenal gland was performed 5 months after diagnosis. Postsurgical chemotherapy protocols was similar with the previous. OUTCOMES: The patient died 2 years after initial diagnosis after 8 relapses following combinational chemotherapy. LESSONS: This case of neuroblastoma is with pronounced somatic mutations but unidentified driver gene and therapeutic target. Although NGS is a potentially powerful tool to guide precision medicine, at current stage, its application in the clinic certainly has its limits. The underlying mechanism of the substantially increased SNV number, as well as the malignant behaviors of the tumor, is yet to be revealed.